Invasive Mucormycosis in Patients with Hemoblastosis in St.-Petersburg - S. N. Khostelidi; A. G. Volkova; M. O. Popova; T. S. Bogomolova; A. S. Kolbin; E. G. Boychenko; N. V. Medvedeva; E. I. Podoltseva; A. V. Klimovich; M. B. Belogurova; I. S. Zuzgin; L. S. Zuborovskaya; et al. (Антибиотики и Химиотерапия, 2020)
Thirty four patients with mucormycosis in 10 hospitals of St. Petersburg were observed in 2004-2013. The most frequent underlying diseases of mucormycosis were acute leukoses (64%). In 100% of the patients mucormycosis developed as a nosocomial infection. The risk factors, etiology, basic clinical signs and strategy in the treatment of mucormycosis were analyzed.